An activity-based fluorescent sensor for the detection of the phenol sulfotransferase SULT1A1 in living cells. Issue 3 (15th March 2021) - Baglia, Regina A.; Mills, Kira R.; Mitra, Koushambi; Tutol, Jasmine N.; Ball, Darby; Page, Kierstin M.; Kallu, Jyothi; Gottipolu, Sriharika; D'Arcy, Sheena; Nielsen, Steven O.; Dodani, Sheel C.
Abstract : Here, we report the development, computational modeling, in vitro enzymology, and biological application of an activity-based fluorescent sensor for the human phenol sulfotransferase SULT1A1. Abstract : Human phenol sulfotransferases mediate the transfer of a sulfuryl moiety from the activated sulfate donor PAPS to hydroxy-containing substrates, altering substrate solubility and charge to affect phase II metabolism and cell signaling. Here, we present the development, computational modeling, in vitro enzymology, and biological application of STS-3, an activity-based fluorescent sensor for the SULT1A1 isoform.